PERSEPSI MASYARAKAT TENTANG PENGOBATAN TRADISIONAL - Fudhla, Anifa; Dewi, Ari Pristiana; Utomo, Wasisto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Traditional medicine is one of the typical Indonesia treatments which mostly comes from values and skills from generation to generation. Most people still use traditional medicine to maintain health and treat diseases until now. 40% of Indonesians choose to use traditional medicine to maintain health and treat diseases. This study aims to determine perceptions of the community of traditional medicine in Tangkerang Selatan Village. The method that is used is descriptive correlation with the cross sectional approach. The research sample were 108 respondents taken based on inclusion criteria using cluster and proposionate sampling. The measuring instrument used questionnaire. Analysis of the data using univariate to determine the frequency distribution. The results showed that of 57 respondents (52.8%) who had a positive perception of traditional medicine and 51 respondents (47.2%) who had negative perceptions of traditional medicine. Health promotion workers in health centers are expected to can provide information about traditional medicine and traditional health services available in the community.Keywords: Traditional Medicine, Perception, Community